Effects of intercalated mono-, di- and triethanolammonium cations on the structural and surface characteristics of sodium form of bentonite - Elkhalifah, A.E.I. (Trans Tech Publications Ltd, 2014)
The present study investigates the effects of intercalation process of protonated primary, secondary and tertiary amines on structural and surface characteristics of sodium form of bentonite clay. For this purpose, sodium form of bentonite clay was prepared and then exchanged with mono-, di- and triethanolammonium cations via intercalation mechanism into the interlayer space of the clay. The prepared samples were characterized by XRD and BET techniques. An increase in the dspacing of bentonite clay with the molar mass of amines was observed in their x-ray diffractograms, following the order of: triethanolamine > diethanolamine > monoethanolamine. The BET results showed a gradual decrease in the BET surface area with the increase in the molar mass of amines used. Based on the results obtained, it can be concluded that the molar mass of amines has significant effects on structural and surface properties of bentonite clay. Â© 2014 Trans Tech Publications, Switzerland.